2013
DOI: 10.3233/iks-130215
|View full text |Cite
|
Sign up to set email alerts
|

A multi-criteria framework for assessing scholarship based on Boyer's scholarship model

Abstract: Universal, effective, fair, and consistent methods for evaluating faculty scholarly activities have remained elusive for years. This research utilized the Analytic Hierarchy Process (AHP) to assess the professoriate's own perceptions of the appropriate assessment of faculty research. The paper also incorporated the Boyer model of scholarship as one of the main criteria for scholarship evaluation. We addressed the "how" and "how much" in the weighting of scholarship output based on a survey of faculty at five C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…8. The third section of the questionnaire was designed to collect data for use in an accompanying AHP study, which is reported in a companion paper (Uzoka, Fedoruk, Osakwe, Osuji, & Gibb, 2013). The complexity of the third section of the questionnaire may have affected the response rate.…”
Section: Resultsmentioning
confidence: 99%
“…8. The third section of the questionnaire was designed to collect data for use in an accompanying AHP study, which is reported in a companion paper (Uzoka, Fedoruk, Osakwe, Osuji, & Gibb, 2013). The complexity of the third section of the questionnaire may have affected the response rate.…”
Section: Resultsmentioning
confidence: 99%
“…The normalized vector matrix is obtained using equation ( 4), where a ji represents the element at row j and column i of the respective symptom versus symptom comparison matrix. Finally, the relative weight or weighted eigenvector, W i is computed using equation ( 5) as the row average of the resulting normalized matrix such that P n i¼1 W i ¼ 1: For consistency analysis, equations ( 6) and (7) were used to estimate the consistency index (CI) and consistency ratio (CR) of each performance matrix, using Saaty's random consistency index (RI) estimates in Table 6, where n is the number of symptoms. If CR ≤ 0:1, the level of inconsistency is acceptable, else the inconsistency is high and the decisionmaker is advised to revise the elements of a ij to realize a more consistent matrix.…”
Section: Ahp Modeling For Febrile Disease Diagnosismentioning
confidence: 99%
“…MCDA methods aid decision-making by considering multiple criteria, 5 delineating conditions, their importance, and influence. 6,7 Abdullah et al 8 defines these methods as techniques for evaluating and selecting alternatives based on various criteria. In healthcare, selecting an appropriate MCDA method is crucial for intelligent systems aiding medical decisions.…”
Section: Introductionmentioning
confidence: 99%